2002
DOI: 10.1038/sj.mp.4000962
|View full text |Cite
|
Sign up to set email alerts
|

Association between a serotonin transporter promoter region polymorphism and mood response during tryptophan depletion

Abstract: This study investigated the relationship between depressive symptom response during tryptophan (TRP) depletion and a functional polymorphism of the promoter region of the serotonin (5-HT) transporter gene (SLC6A4). 1 Forty-three subjects in remission from a major depressive episode who underwent TRP depletion were genotyped. DNA was extracted from blood lymphocytes or from cheek cells. 2 The two common alleles are designated long (l) and short (s). Depressive symptoms were measured with the 25-item Hamilton De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 31 publications
4
58
1
Order By: Relevance
“…In addition to not having many clinical relapse predictors, our subjects may not be genetically predisposed to a depressive response after tryptophan depletion. A recent study by Moreno et al (2002) showed an association between a particular genotype in the promoter region of the serotonin trans- Figure 2. Mean free plasma tryptophan levels at 2:30 P.M., 10:30 P.M., and 7 A.M. on the control and experimental days (values given are means Ϯ SEM, n ϭ 8) with a significant interaction effect between the factors of day and time (F 2,14 ϭ 19.32, p ϭ .00009) porter gene and a depressive response to tryptophan depletion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to not having many clinical relapse predictors, our subjects may not be genetically predisposed to a depressive response after tryptophan depletion. A recent study by Moreno et al (2002) showed an association between a particular genotype in the promoter region of the serotonin trans- Figure 2. Mean free plasma tryptophan levels at 2:30 P.M., 10:30 P.M., and 7 A.M. on the control and experimental days (values given are means Ϯ SEM, n ϭ 8) with a significant interaction effect between the factors of day and time (F 2,14 ϭ 19.32, p ϭ .00009) porter gene and a depressive response to tryptophan depletion.…”
Section: Discussionmentioning
confidence: 99%
“…These mice show reduced 5-HT tissue concentrations and increased extracellular concentrations of 5-HT in the striatum and probably other structures (for review see Murphy et al 51 ). The l-allele of the 5-HTTLPR polymorphism is associated with better SSRI antidepressive effects than the s-allele 49,52,53 and with faster response to several SSRI's. 54,55 Combined treatment with a 5-HT 1A blocker to prevent negative feedback at the somatodendritic level compensated for the worse antidepressant effect of SSRIs in s/s and s/l genotypes, 56 suggesting higher 5-HT 1A negative feedback in s-allele genotypes.…”
Section: -Ht Transportermentioning
confidence: 97%
“…Some studies reported no association, 39,43,44 others found an association between the s-allele and depression, 26,[45][46][47][48] while others conclude that the l-allele is associated with depression. 49 However, most evidence seems to suggest an association between the s-allele of 5-HTTLPR and depression. The lower 5-HT uptake activity caused by the s-allele may result in increased levels of 5-HT in the vicinity of the 5-HTergic cell bodies and dendrites in the raphe complex.…”
Section: -Ht Transportermentioning
confidence: 99%
“…Among individuals with a history of depression, the ll phenotype is consistently associated with more severe mood deterioration during tryptophan depletion. 89,90 On the other hand, among individuals without personal history of depression, the effect of TD is smaller, includes changes in anxiety, punishment sensitivity and motivation rather than mood and is more pronounced among ss homozygotes. [91][92][93][94] Neumeister and colleagues 90 proposed a model explaining this apparent interaction of 5-HTTLPR with personal history of depression by differential activity of pre-and postsynaptic 5-HT1A and 5-HT1B receptors.…”
Section: The Functionality Of 5-httlprmentioning
confidence: 99%